Editorial - Organizing & Evaluation Committee (Brazilian Journal of Production Engineering, 2026)
The VII Production Engineering Symposium (SIENPRO), promoted by the Postgraduate Program in Production Engineering (PPGEP) and the undergraduate program in Production Engineering at the Federal University of Catalão (UFCAT), is a national scientific, technological, and innovation event aimed at strengthening teaching, research, extension, and cultural activities. The target audience includes undergraduate and postgraduate students, professors, researchers, engineers, entrepreneurs, and other professionals in Production Engineering and related fields. Held from October 29th to 31st, 2025, its theme was "Innovation, Sustainability, and Entrepreneurship: Paths to the Transformation of Production Engineering." The event aimed to promote integration between academia, the productive sector, and society, fostering the exchange of knowledge, experiences, and innovative solutions, as well as the development of technical and analytical skills aligned with contemporary challenges in the field. The activities developed, such as lectures, short courses, roundtables, and other training actions, provided a collaborative and interdisciplinary environment, stimulating scientific debate, innovation, and the practical application of technologies, methods, and tools of Production Engineering. Finally, the articles selected for this special edition of the Brazilian Journal of Production Engineering (BJPE) reflect the thematic diversity and scientific quality of the works presented at the VII SIENPRO, contributing to the advancement of knowledge, the strengthening of applied research, and the scientific dissemination in Production Engineering and related areas.